2007
DOI: 10.1593/neo.07661
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation and Aberrant Expression of the Glioma Pathogenesis-Related 1 Gene in Wilms Tumors

Abstract: Wilms tumors (WTs) have a complex etiology, displaying genetic and epigenetic changes, including loss of imprinting (LOI) and tumor suppressor gene silencing. To identify new regions of epigenetic perturbation in WTs, we screened kidney and tumor DNA using CpG island (CGI) tags associated with cancer-specific DNA methylation changes. One such tag corresponded to a paralog of the glioma pathogenesis-related 1/related to testis-specific, vespid, and pathogenesis proteins 1 (GLIPR1/RTVP-1) gene, previously report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 35 publications
1
37
1
Order By: Relevance
“…Altered global DNA methylation patterns, specifically hypomethylation, have been reported for many cancers [27][28][29][30][31] including HCC [32]. However, whether HBV or HBx was involved in epigenetic modification during HCC carcinogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Altered global DNA methylation patterns, specifically hypomethylation, have been reported for many cancers [27][28][29][30][31] including HCC [32]. However, whether HBV or HBx was involved in epigenetic modification during HCC carcinogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…WT has a complex etiology and is associated with both genetic and epigenetic changes (262)(263)(264)(265)(266). Using a comparative analysis of differentially methylated regions in the genomes of normal fetal and WT kidney tissue, Chilukamarri et al (267) identified the GLIPR1 promoter as being a frequently hypomethylated locus in WT. Consistent with this, GLIPR1 mRNA and proteins were significantly up-regulated in the majority of WT tissues examined (267).…”
Section: Cap Proteins In Cancermentioning
confidence: 99%
“…Furthermore, CpG methylation density is very important due to a fact that low-density CpG methylation would merely repress a weak promoter, while high-density methylation is required for inhibition of a strong promoter (Bird, 1992). Global hypomethylation (Esteller and Herman, 2002) and regional promoter CGIs hypomethylation (Chilukamarri et al, 2007;Lin et al, 2007b;Kim et al, 2008) may activate proto-oncogenes, loss gene imprinting, and reactivate transposable elements. Nevertheless, hypermethylated CGIs may suppress the expression of genes that contribute to tumor suppression, chromatin condensation, and DNA repair (Baylin, 2005).…”
Section: Hypermethylation and Hypomethylation In Lung Cancermentioning
confidence: 99%